Application of John Dewey's Thinking Concept in Improving the Function of Museums as a Learning Resource - Ambar Rejiyanti; Rhoma Dwi Ari Yuliatri (International Journal Labs, 2026)
John Dewey's views on educational progressivism have significantly influenced educational practices in Indonesia. This research examines John Dewey's philosophical thought, which introduces a new paradigm for understanding the concept of learning. Dewey emphasised that education must be continuous and marked by ongoing innovation in order to achieve progress, encompassing the development of critical thinking skills, problem-based education, contextual learning, active learning, and experience as the foundation of learning. Dewey's concepts are also relevant to museums, as museums serve as evolving learning resources that function as centres of collective knowledge reflecting a nation's civilisation. This research employs a qualitative method with a literature review approach, examining various sources related to Dewey's thought and the educational role of museums. The findings reveal six key areas in which Dewey's concepts align with museum functions: learning through experience (learning by doing), experience-based education (experiential education), visitor-centred learning, reflective thinking, education as a social and democratic process, and the integration of knowledge according to scientific context. These findings demonstrate that Dewey's progressivist philosophy provides a strong theoretical foundation for optimising museums as active, participatory learning resources rather than as passive repositories of artefacts.